The occurrence of pulmonary hypertension in patients with thalassemia major - Hasan Basri; Armijn Firman; Kusnandi Rusmil; Eddy Fadlyana (Paediatrica Indonesiana, 2003)
Background The life of patients with thalassemia major dependson blood transfusions, while repeated blood transfusions may causeadverse effects such as iron deposition in various organs, includ-ing heart and lungs, which eventually increases the pulmonaryarterial pressure.Objective This study was proposed to know the occurrence ofpulmonary hypertension in patients with thalassemia major, mea-sured by echocardiography in the Thalassemia Clinic, Departmentof Child Health, Medical School, Padjadjaran University/HasanSadikin Hospital, Bandung.Methods A descriptive cross-sectional study was carried outon 30 patients with thalassemia major, aged 10-14 year-old whoreceived repeated blood transfusions. The study was conductedfrom April to May 2002. Subjects were examined right after ablood transfusion completed and the pulmonary arterial pres-sure was assessed using Doppler–echocardiography and 2-Dechocardiography.Results Twenty two out of 30 subjects showed pulmonary hyper-tension, with pulmonary arterial pressure ranged between 32.3 to46.2 mmHg. According to the age group, pulmonary hypertensionwas found in 12 out of 17 subjects aged 10-12 years old and 10out of 13 subjects aged 13-14 years old.Conclusion The occurrence of pulmonary hypertension in patientswith thalassemia major at Hasan Sadikin Hospital was 22/30 andseemed to increase with the age of the patients